Association Between Modic Changes and Low Back Pain in Middle Age: A Northern Finland Birth Cohort Study. Issue 19 (1st October 2020) - Saukkonen, Jesperi; Määttä, Juhani; Oura, Petteri; Kyllönen, Eero; Tervonen, Osmo; Niinimäki, Jaakko; Auvinen, Juha; Karppinen, Jaro
Abstract : Study Design: A cross-sectional study of the Northern Finland Birth Cohort 1966 (NFBC1966). Objective: The aim of this study was to evaluate the association between the type, size, and location of lumbar Modic changes (MC), and prolonged disabling low back pain (LBP). Summary of Background Data: LBP is the leading cause of disability worldwide and it affects all age- and socioeconomical groups. Only a small proportion of LBP patients are diagnosed with a specific cause: In most cases no single nociceptive cause for the pain can be identified. MC are visualized in magnetic resonance imaging (MRI) as a signal intensity change in vertebral bone marrow and have been proposed to represent a specific degenerative imaging phenotype associated with LBP. MC can be classified into several subtypes, of which inflammatory Type 1 (MC1) is suggested as being more likely to be associated with LBP. Methods: We assessed lumbar MRI (n = 1512) for the presence, type, and size of MC. The associations of MC characteristics with prolonged (≥30 days during the past year) and disabling (bothersomeness of LBP at least 6 on a 0–10 Numeric Rating Scale) LBP, evaluated at the time of imaging at 47 years, were analyzed using binary logistic regression, adjusted for sex, BMI, smoking, educational status, lumbar disc degeneration, and disc herniations. Results: Any MC and MC1 were associated with prolonged disabling LBP (odds ratio [OR] after full adjustments 1.50 [95% confidence interval, CI 1.05–2.15] and 1.50 [95% CI 1.10–2.05], respectively). Furthermore, MC covering the whole anterior-posterior direction or the whole endplate, as well as the height of MC, were significantly associated with prolonged disabling LBP (OR after full adjustments 1.59 [95% CI 1.14–2.20], 1.67 [95% CI 1.13–2.46] and 1.26 [95% CI 1.13–1.42], respectively). Conclusion: Our study showed a significant and independent association between MC and clinically relevant LBP. Level of Evidence: 3 Abstract : This large-scale birth cohort study found that Modic changes were independently associated with disabling low back pain, and that the type and size of the changes affected this association.